The Art of Reading: Contexts for Writing - Gould, Eric. (New York McGraw-Hill Publishing Company, 1990)
The Art of Reading aims to involve students directly and immediately in the process of intellectual inquiry. Active, engaged reading develops the writers resources and resourcefulness; and active, engaged writing stimulates and clarifies the readers responses to texts.
Keywords: Writing